2018
DOI: 10.3389/fmicb.2018.01674
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Analysis Reveals Seasonal Variation of the Gut Microbiota Composition Within Forest Musk Deer (Moschus berezovskii)

Abstract: The gut microbiota plays a key role in the nutritional ecology of ruminants, and host diet has a significant effect on these microbial communities. Longitudinal studies assessing variation of seasonal microbiota in animals can provide a comparative context for interpreting the adaptive significance of such changes. However, few studies have investigated the effects of seasonally-related dietary shifts on the gut microbial communities of endangered forest musk deer (FMD), and the national breeding programs need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 59 publications
8
38
0
Order By: Relevance
“…The core bacterial phyla in both musk deer species were Firmicutes and Bacteroidetes, which is consistent with previous studies of the microbiota of musk deer [18,25,26] and other ruminants [27][28][29]. The phyla are found in the guts of many mammals, which suggest the importance of these bacteria in the gut ecosystem [30].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The core bacterial phyla in both musk deer species were Firmicutes and Bacteroidetes, which is consistent with previous studies of the microbiota of musk deer [18,25,26] and other ruminants [27][28][29]. The phyla are found in the guts of many mammals, which suggest the importance of these bacteria in the gut ecosystem [30].…”
Section: Discussionsupporting
confidence: 89%
“…We characterized the seasonal variation in the gastrointestinal microbiota of Siberian musk deer and forest musk deer using high-throughput sequencing of the 16S rRNA gene in fecal samples. According to the research results of Hu et al [18] that the in uence of seasonal factors on the gut microbiota of forest musk deer, and daily food of the siberian musk deer have obvious seasonal changes, we selected representative winter and summer seasons for this research.The main objectives of present study are: (1) to compare the composition and diversity gut microbiota of two species; (2) to determine seasonally (i.e., summer and winter) variations in the microbial community composition and disease of Siberian musk deer; (3) to examine the changes in signaling pathways and functional genes, and; (4) to discuss their potential functions in the diagnosing diseases of the digestive system and for improving feeding methods.…”
mentioning
confidence: 99%
“…The effect of seasonality on both diet and the microbiome has only recently been explored in the current literature. Free ranging animal models have suggested that seasonality may affect the function and composition of the gut microbiota [87,88] in response to a seasonal change in diet. In 2017, researchers collected 350 faecal samples from the Tanzanian Hadza tribe over the span of a year [76].…”
Section: Evidence For Long Lasting Effect Of Diet On the Gut Microbiomementioning
confidence: 99%
“…It provides insight into evolutionary history, and the bacterial community demonstrates phenotypic plasticity that affects the host's capacity to adapt to changing environmental pressures (Antwis et al, ; Bahrndorff et al, ; Girard et al, ). In mammals, the gastrointestinal microbiome has been shown to be affected by captivity (Li et al, ), kinship (Yuan et al, ), disease (Wasimuddin et al, ), and season (Hu et al, ). More specifically, many comprehensive microbiome studies have been performed on ungulate species because their unique morphological traits impact the gut bacterial composition, and in return, the bacterial composition impacts fitness (Bergmann et al, ; Gruninger, Sensen, McAllister, & Forster, ; Koike, Yoshitani, Kobayashi, & Tanaka, ; Li et al, ; Pope et al, ; Qi et al, ; Salgado‐Flores, Bockwoldt, Hagen, Pope, & Sundset, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this general similarity among herbivores, the relative abundance of the bacteria making up the microbiome differs between individuals and can be artificially altered by changing factors of diet (Escobar‐Zepeda, De León, & Sanchez‐Flores, ; Koike et al, ; Tian, Wu, Chen, Yu, & He, ). In some populations, diet is altered by shifting seasons and both diet and seasonality have been documented to influence the bacteria community structure in ruminants, including forest musk deer (Hu et al, ), and muskoxen (Ungerfeld, Leigh, Forster, & Barboza, ). While ungulate and ruminant microbiomes have been generally well‐studied, there is little information on population‐level microbiome variation in these species.…”
Section: Introductionmentioning
confidence: 99%